Medication Errors: A Review of Classifications - Praneetha Palasuberniam; Chin Suliong; Viknesvaran Thangiah; Urban John Arnold D'Souzaa (2018)
Medication errors (MEs) are preventable mistakes that occur when there is a failure in the treatment process of any disease that can cause potential harm to patients. Having an effect on patients, health outcomes and costs incurred, it does burden our economically-developing country. Database systems have been created worldwide for the reporting of MEs, but varying countries practise different classifications of MEs hence it poses a challenge to categorize them. This makes it next to impossible to fully curb this continual problem. There are a number of classifications of MEs, based on mistakes and errors based on skills, based on the mistakes itself, based on symptoms and based on the stages of drug delivery system. This review summarizes the pre-existing classifications of MEs.